Proteome-wide identification of druggable targets and inhibitors for multidrug-resistant Pseudomonas aeruginosa using an integrative subtractive proteomics and virtual screening approach - Divya Vemula; Vasundhra Bhandari (Heliyon)
Pseudomonas aeruginosa, a versatile and antibiotic-resistant gram-negative pathogen, poses a critical threat to both immunocompromised and immunocompetent populations, underscoring the urgent need for new therapeutic targets. This study applies an extensive subtractive proteomics approach to identify viable drug targets within the core proteome of P. aeruginosa PAO1, analyzing a total of 5563 proteins. Through a rigorous, multi-stage process, we excluded human homologs, identified essential proteins, mapped functional pathways, determined subcellular localization, and assessed virulence and resistance factors. This comprehensive analysis led to the identification of three novel, druggable targets integral to P. aeruginosa's pathogenicity and multidrug resistance: preprotein translocase subunit SecD, chemotaxis-specific methyl esterase, and imidazole glycerol phosphate synthase subunit HisF2. Following this, inverse virtual screening of 464,867 compounds from the VITAS-M library, performed using Schrödinger's Glide module, initially pinpointed 15 potent hits with favorable binding affinities and pharmacokinetic profiles as confirmed by QikProp analysis. Subsequent molecular dynamics, MMPBSA and DFT calculations refined these to three promising candidates: STK417467 for imidazole glycerol phosphate synthase subunit HisF2, STL321396 for chemotaxis-specific methylesterase, and STL243336 for preprotein translocase subunit SecD. These compounds show strong potential as inhibitors and could be developed further as therapeutic agents against multidrug-resistant P. aeruginosa infections. This study provides a robust computational framework for the discovery of drug targets and candidate inhibitors, marking a significant step toward effective treatments for resistant Pseudomonas infections.